Population Structure and Genetic Diversity Within the Endangered Species Pityopsis ruthii (Asteraceae) - Hatmaker, E. Anne; Staton, Margaret E.; Dattilo, Adam J.; Hadziabdic, Ðenita; Rinehart, Timothy A.; Schilling, Edward E.; Trigiano, Robert N.; Wadl, Phillip A. (Frontiers in Plant Science, 2018)
Pityopsis ruthii (Ruth’s golden aster) is a federally endangered herbaceous perennial endemic to the Hiwassee and Ocoee Rivers in southeastern Tennessee, USA. Comprehensive genetic studies providing novel information to conservationists for preservation of the species are lacking. Genetic variation and gene flow were evaluated for 814 individuals from 33 discrete locations using polymorphic microsatellites: seven chloroplast and twelve nuclear. A total of 198 alleles were detected with the nuclear loci and 79 alleles with the chloroplast loci. Gene flow was estimated, with the Hiwassee River (Nm= 2.16; FST= 0.15) showing higher levels of gene flow and lower levels of population differentiation than the Ocoee River (Nm= 1.28; FST= 0.19). Population structure was examined using Bayesian cluster analyses. Nuclear and chloroplast analyses were incongruent. From the chloroplast microsatellites, three clusters were identified; all were present in sampling sites at both rivers, indicating a lack of allele fixation along rivers. Nuclear markers revealed two clusters and separated by river. When the Hiwassee River locations were analyzed, four clusters were identified for both the chloroplast and nuclear microsatellites, though the individuals clustered differently. Analysis of the Ocoee River revealed two clusters for the chloroplast microsatellites and three for the nuclear microsatellites. We recommend P. ruthii be managed as four populations for the Hiwassee River and three populations for the Ocoee River. Our results provide critical genetic information for P. ruthii that can be used for species management decisions to drive future population augmentation/reintroduction and ex situ conservation efforts.